Convergent synthesis of the tetrasaccharide repeating unit of the O-antigen of Shigella boydii type 9 - Santra, Abhishek; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2011)
A convenient synthesis of the tetrasaccharide repeating unit of the O-antigen of Shigella boydii type 9 has been achieved in excellent yield using a [2 + 2] block glycosylation strategy. TEMPO-mediated selective oxidation of the primary alcohol of the tetrasaccharide derivative 8 to the carboxylic group followed by deprotection of the functional groups furnished target tetrasaccharide 1 as its 4-methoxyphenyl glycoside in high yield.
Keywords: diarrhea; glycosylation; O-antigen; oligosaccharide; Shigella boydii